(NfIZI^ESKIE QWLENIQ W DNEWNYH POLQRNYH KASPAH (B/s - (NpUDOWKIN(B, (Nm(B.(Ni(B.s; (NkLEJMENOWA(B, (Nn(B.(Ng(B.s; (N{ALIMOW(B, (Ns(B.(Nl(B.s; (NlIPEROWSKIJ(B, (NwIKTOR aNDREEWI^s ((NmOSKWA (B:s (Nan sssr(B. (NmEVDUWEDOMSTWENNYJ GEOFIZI^ESKIJ KOMITET(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 109-125s
(NzAGL(B. (NNA DOP(B.(NTIT(B.(NL(B.: Physical phenomena in the daytime polar cusps.s
(NrEZ(B.: (NANGL(B.s
Keywords: (NmAGNITNOE POLE zEMLIs; (NfIZIKAs